Constructing Teacher Work Quality in Public Secondary Schools: A Qualitative Study of Instructional Supervision, Pedagogical Competence, and Work Discipline - Try Susanti; Sumirah Sumirah (GHAITSA : Islamic Education Journal, 2026)
This study explores how teachers in public secondary schools construct work quality regarding instructional supervision, pedagogical competence, and work discipline. A qualitative case study involved 25 science and mathematics teachers from five schools in Jambi Province, Indonesia, selected through purposive maximum variation sampling. Data were collected via semi-structured interviews, participant observation, and document analysis, then analyzed using thematic analysis. Findings reveal teachers construct work quality as multidimensional: professional responsibility toward student outcomes, continuous learning, relational collaboration, and integration of spiritual values—particularly Islamic amanah (trust), ibadah (worship), and ikhlas (sincere intention). Instructional supervision is perceived supportive only when developmental, relational, and action-oriented, yet quality varies due to principal training gaps, geographical constraints, and infrastructure disparities. Pedagogical competence is understood as an ongoing developmental journey hindered by limited training access, heavy workloads, and non-linear teaching assignments. Work discipline involves external compliance and internal commitment, shaped by geographical, personal, and structural factors rather than merely individual character. The study concludes teacher work quality is a contextually situated achievement constructed through ongoing negotiation between personal values, professional experiences, institutional demands, and cultural-religious frameworks, with implications for context-sensitive teacher development policies.